Toksisitas Insektisida Organofosfat Dan Karbamat Terhadap Nyamuk Aedes aegypti - Endang Puji Astuti; Rita Juliawati (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
Aedes aegypti mosquito is increasing problem of public health, being the vector responsible for Dengue and Chikungunya. Chlorpirifos (Organofosfat) and Metonil (Carbamate) were known to posses insecticide activity against insect. The study was aimed to examine effectiveness of Chlorpirifos and Metonil as insectiside against Ae. aegypti mosquitoChlorpirifos a significantly higher insecticide activity against Ae. aegypti than Metonil. The mosquito mortality was observed after 24 h exposure. The LC50 value of Chlorpirifos and Metonil were 0.64 mg/lt and 0,802 mg/lt, against Ae. aegypti mosquito. The mixed of both insecticide was LC50 value 108.04 mg/lt, this result prove that mixed of both insecticede not sinergism. The result of this study suggested that Chlorpirifos more effective insecticide against Ae. aegypti than Metonil.